A novel injury site‐natural antibody targeted complement inhibitor protects against lung transplant injury. Issue 6 (26th February 2021) - Li, Changhai; Patel, Kunal; Tu, Zhenxiao; Yang, Xiaofeng; Kulik, Liudmila; Alawieh, Ali; Allen, Patterson; Cheng, Qi; Wallace, Caroline; Kilkenny, Jane; Kwon, Jennie; Gibney, Barry; et al.
Abstract : Complement is known to play a role in ischemia and reperfusion injury (IRI). A general paradigm is that complement is activated by self‐reactive natural IgM antibodies (nAbs), after they engage postischemic neoepitopes. However, a role for nAbs in lung transplantation (LTx) has not been explored. Using mouse models of LTx, we investigated the role of two postischemic neoepitopes, modified annexin IV (B4) and a subset of phospholipids (C2), in LTx. Antibody deficient Rag1‐/‐ recipient mice were protected from LTx IRI. Reconstitution with either B4 or C2nAb restored IRI, with C2 significantly more effective than B4 nAb. Based on these information, we developed/characterized a novel complement inhibitor composed of single‐chain antibody (scFv) derived from the C2 nAb linked to Crry (C2scFv‐Crry), a murine inhibitor of C3 activation. Using an allogeneic LTx, in which recipients contain a full nAb repertoire, C2scFv‐Crry targeted to the LTx, inhibited IRI, and delayed acute rejection. Finally, we demonstrate the expression of the C2 neoepitope in human donor lungs, highlighting the translational potential of this approach. Abstract : Targeted complement inhibition protects the lung against ischemia‐reperfusion injury.